An overview of learning content in MyLexics (an assistive multimedia courseware for dyslexics) - Mohd. Yusoh, Zeratul Izzah; Devaraju, Anusuriya; Zakaria, Mohd Hafiz; Techanamurthy, Umawathy (2008)
One of the most promising areas of education is the development of computer-based teaching materials, especially interactive multimedia programs. Interactive multimedia allows independent and interactive learning, and yet presents the learning information to the learners in newly engaging and meaningful ways. This paper delivers the theoretical concepts and design of a multimedia courseware called ‘MyLexic’. ‘MyLexic’ is the first learning tool to nurture interest on Malay language basic reading among preschool dyslexic children in Malaysia. The theoretical framework proposed in the study is based on research in dyslexia theory with Dual Coding Theory, Structured Multi-sensory Phonic Teaching and Scaffolding instructional technique. Detail explanations on its learning content are also discussed. The courseware is hoped to contribute a significant idea to the development of technology in Malay language education for dyslexics in Malaysia.